2021
DOI: 10.3390/land10080781
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Impact of Land Circulation on the Income Gap of Rural Households: Evidence from CHIP

Abstract: With the continued development of the economy, the income gap among Chinese rural households continues to widen. The land system plays a decisive role in developing “agriculture, rural areas and farmers” and land circulation is a factor in the increase in income inequality among farm households. Based on the 2013 China Household Income Project (CHIP), this article used the re-centered influence function (RIF) regression method to empirically test the impact of rural land circulation on the income gap of rural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
(13 reference statements)
1
18
1
Order By: Relevance
“…A primary objective of the agenda is not only to illuminate the conditions of possibility that enable Chinese urbanization, but also to identify the 10 Land circulation refers to peasants' transference of agricultural land use rights to other peasants or organizations in return for compensation. A study by Huo and Chen (2021) reveals that land circulation has grown from less than 1% of total cultivable land in 1984 to 35.9% in 2019. This sharp growth indicates that a substantial proportion of the peasantry no longer farms directly but retains the right to do so.…”
Section: Discussionmentioning
confidence: 99%
“…A primary objective of the agenda is not only to illuminate the conditions of possibility that enable Chinese urbanization, but also to identify the 10 Land circulation refers to peasants' transference of agricultural land use rights to other peasants or organizations in return for compensation. A study by Huo and Chen (2021) reveals that land circulation has grown from less than 1% of total cultivable land in 1984 to 35.9% in 2019. This sharp growth indicates that a substantial proportion of the peasantry no longer farms directly but retains the right to do so.…”
Section: Discussionmentioning
confidence: 99%
“…Drawing on the practice of existing research [ 31 ], the logarithm of the total per capita income of rural households is used to reflect the income level of rural households, and the Gini coefficient of the total per capita income of rural households is used as an indicator to measure the income gap of rural households.…”
Section: Data Models and Variablesmentioning
confidence: 99%
“…In general, household financial vulnerability mainly includes aspects such as over-indebtedness and emergency savings, and its specific measures are mostly related to income, liabilities, and assets (Fuenzalida and Ruiz-Tagle, 2011;Loke, 2017;Noerhidajati et al, 2021). Previous studies have shown that the farmland property rights reform and transfer in rural China can not only effectively improve the income level of farm households (Peng et al, 2020;Yang et al, 2020;Huo and Chen, 2021), but also explore the transformation of the financial value of farmland (Liu and Li, 2015;Jiang et al, 2017). The transformation of the financial value of farmland can further increase the liquidity of household capital, improve the efficiency of household asset allocation, and strengthen the ability of farms to cope with various uncertain risks.…”
Section: Research Hypotheses the Association Between Farmland Circu...mentioning
confidence: 99%
“…According to the sustainable livelihoods framework proposed by the Department for International Development (DFID, 2022), farmland circulation is also a livelihood strategy for farmers that has an impact on their household livelihood outcomes. Numerous studies have discussed the impact of farmland circulation on the livelihood outcomes of households from different perspectives, such as income (Peng et al, 2020;Yang et al, 2020;Huo and Chen, 2021), consumption (Lei and Zhu, 2021;Zeng et al, 2022), quality of life (Zhang et al, 2018;, and subjective wellbeing (Qiu et al, 2021), providing the basis for further research. It is worth noting that vulnerability is also a core indicator of livelihood outcomes in the sustainable livelihoods analysis framework and that reducing vulnerability or strengthening resistance to vulnerability is intrinsic to securing the livelihoods of farm households (Guo and Wang, 2021;DFID, 2022), with financial vulnerability being an important research perspective for analyzing the wellbeing of farm households, financial risks, and vulnerability levels.…”
Section: Introductionmentioning
confidence: 99%